A theoretical approach to photosynthetically active radiation silicon sensor - Tamasi, Mariana Julia Luisa (2013)
Fil: Tamasi, Mariana Julia Luisa. Comisión Nacional de Energía Atómica. Departamento de Energía Solar; Argentina